Gold Nanorod Surface-Enhanced Raman Spectroscopy Substrate for l-DOPA Detection: Experimental and Theoretical Approaches - de Oliveira, Tatiana Ap. [UNESP]; S. Martin, Cibely [UNESP]; J.G. Rubira, Rafael [UNESP]; de Barros, Anerise; Mazali, Italo O.; Zidoi, Luiz P. [UNESP]; Batagin-Neto, Augusto [UNESP]; Constantino, Carlos J.L. [UNESP] (SAGE Publications, 2025)
Experimental efforts aimed at detecting levodopa (l-DOPA) using surface-enhanced Raman scattering (SERS) face a persistent challenge in obtaining a SERS signal with negatively charged nanoparticles. This challenge stems from the repulsion between deprotonated l-DOPA in aqueous solution and the charged surface of the nanoparticles, revealing dependencies on time and concentration to achieve the SERS signal. This study explores the adsorption mechanism of l-DOPA on the surface of gold nanorods (AuNRs) covered with a cetrimonium bromide (CTAB) bilayer as a colloidal solution, subsequently dried onto a solid substrate such as glass, silicon, and Au substrate. Experimental findings are supported by density functional theory theoretical calculations. The comparison between experimental and theoretical results highlights that the SERS profile can be attributed to the adsorption of l-DOPA via the catechol ring, leading to the formation of anionic and dianionic species.
Keywords: density functional theory; detection; DFT; gold nanoparticles; l-DOPA; SERS; surface-enhanced Raman spectroscopy